The Influence of Competence and Internal Control on Financial Reporting of Southeast Sulawesi Provincial Hospital - Husin, Husin; Mirosea, Nitri; Fitriyani, Fitriyani (International Journal of Management and Education in Human Development, 2021)
This study aims to analyze the influence of competence and internal control system on the quality of financial reporting at Bahteramas General Hospital in Southeast Sulawesi Province. The method of data collection used is questionnaire data. The samples in this study were all employees of the finance department of Bahteramas Hospital of Southeast Sulawesi Province which amounted to 40 employees. The analysis technique uses multiple linear regression analysis t test (partial test) and F test (simultaneous test) and determination coefficient test. The results of this study showed that partially and simultaneously the competence and internal control system had a positive and significant effect on the quality of financial reporting at the Bahteramas General Hospital in Southeast Sulawesi Province.